Kinematics Model of a Novel 6-DOF Redundancy Hybrid Machine Tool - Liu Na; Mei Ying; Wang Shusen; Hu Weiwei (Jixie chuandong)
A structure scheme for a novel 6-DOF hybrid machine tool（ HMT） is proposed. In this scheme,a novel 4-PRP redundantly actuated parallel mechanism is proposed as the position module,which can realize three motion,with assistance of the 3-UPS&PU parallel mechanism,6-DOF machining can be realized. Firstly,the three-dimensional translations and three-dimensional rotations motion of this machine tool are analyzed based on screw theory. Then,the inverse displacement analysis model is provided by using analytical methods and the geometric relation of the mechanism. And the first-order influence coefficient matrix-Jacobian matrix and the second order influence coefficient matrix-Hessian matrix and complete kinematics model are established by using the influence coefficient method. At last,the position inverse solution is obtained by using MATLAB and the results simulation verification is carried out by using ADAMS,which verify that the correctness of the inverse displacement analysis model and the realizability of the mechanism.